AQÍMBET BAQSÍNÍŃ QARAQALPAQ BAQSÍSHÍLÍQ MEKTEPLERINIŃ RAWAJLANÍWÍNDA TUTQAN ORNÍ - Erejepov, A.A. (SCIENCE and SOCIETY, 2024)
The article is devoted to the art of giving and its deep history. We are also talking about Akimbet bakhshi, one of the performers who takes place in Karakalpak bakhshi art. Akimbet bakhshi is mentioned as a singer of his time, who deeply studied folk music and made a great contribution to the development of the Karakalpak art of bakhshi.